High-Efficiency Light-Emitting Diodes of Organometal Halide Perovskite Amorphous Nanoparticles - Xing, Jun (2017)
Organometal halide perovskite has recently emerged as a very promising family of materials with augmented performance in electronic and optoelectronic applications including photovoltaic devices, photodetectors, and light-emitting diodes. Herein, we propose and demonstrate facile solution synthesis of a series of colloidal organometal halide perovskite CH3NH3PbX3 (X = halides) nanoparticles with amorphous structure, which exhibit high quantum yield and tunable emission from ultraviolet to near-infrared. The growth mechanism and photoluminescence properties of the perovskite amorphous nanoparticles were studied in detail. A high-efficiency green-light-emitting diode based on amorphous CH3NH3PbBr3 nanoparticles was demonstrated. The perovskite amorphous nanoparticle-based light-emitting diode shows a maximum luminous efficiency of 11.49 cdA-1, a power efficiency of 7.84 lmW-1, and an external quantum efficiency of 3.8%, which is 3.5 times higher than that of the best colloidal perovskite quantum-dot-based light-emitting diodes previously reported. Our findings indicate the great potential of colloidal perovskite amorphous nanoparticles in light-emitting devices.